The Teaching of Reading as Prophylaxis: the Organic Act of Public Instruction: between charity and instruction - Guzmán Méndez, Diana Paola (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The liberal radicalism that governed national destinies between 1863 and 1886 marked the beginning of a new era for lay, free education in Colombia. The teaching of literature occupied a central space in the liberal plan. Education, higiene and morality formed the triad that fundamentally defined the conception of education and the function of literature and reading as elements of progress. This study attempts to demonstrate that reading was formulated as a prophylaxis, a method of higiene and preventive medicine that traversed time and was installed on two contradictory forms of logic: the sense of charity belonging to the catholic ideology, based on Lancasterian principles, and the logic of instruction based on Pestolazzi, related to the idea of a national body on the path of progress. The reading materials analyzed in this study demonstrate that reading was a moral practice before an educational and knowledge-related one.